Comparative Studies on the Quality and Antimicrobial Effect of the Fruit Oils of Canarium schweinfurthii Engl. (Atili), Dacryodes edulis H.J. Lam (Ube) and Persea americana Mill (Avocado) - Nyam, Mary Azumi; Umaru, Bethel S.; Wonang, David Longwap; Papi, Danladi Yakubu; Adolong, Vincent Alfred (British Journal of Healthcare and Medical Research, 2024)
Increase in consumption of oils from plant origin has led to a wide debate regarding their health effects. This study was undertaken to on three types of fruit oils, Canarium schweinfuthii, Dacryodes edulis and Persea Americana to determine the percentage yield, their phytochemical constituents, cholesterol levels and their microbial effect on some selected fungi and bacteria species. Cold maceration technique using n-Hexane was the extraction method used and the percentage yield was determined. Phytochemical screening and cholesterol levels were determined using standard methods. Antimicrobial activities were carried out on the clinical isolates of the fungi (Aspergillus flavus, Aspergillus fumigatus and Aspergillus terreus) and bacteria (Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa) using disk diffusion techniques. The results of the extraction showed that 300g each of D. edulis had the highest percentage oil yield of 41.71%, followed by C. schweinfuthii, 36.31% and P. Americana had the lowest amount with 18.37%. The phytochemical screening also revealed the presence of secondary metabolites such as steroids, anthraquinones, terpenes and cardiac glycosides, but alkaloids, flavonoids, tannins and saponins were all absent in the oils. The cholesterol analysis showed P. americana having the highest level of 3223.32 mg/ml (3.22%), followed by D. edulis with 3108.69 mg/ml (3.11%) and C. schweinfurthii had the lowest, 2760.86 mg/ml (2.76%). It was observed that the oils had no antifungal activities on the test organisms. The antibacterial activity was in a concentration-dependent manner as S. aureus was the most susceptible to the oils with C. schweinfuthii having the highest activities of 7.77±0.47-10.07±0.00 followed by D. edulis oil 6.67±0.35mm-9.00±0.00mm and P. americana oil which had no activity on the test organism. D. edulis had the highest activity on E. coli 7.47±0.47-10.07±0.00 while C. schweinfurthii and P. americana had no activity on the test organism. D. edulis also had the highest activity of 6.67±0.33-10.33±0.33 which was significantly different from C. schweinfurthii and P. americana which had no activity on the test organism, therefore, at P<0.05, there was a significant difference in the antibacterial activities of the oil. This implies from the study that the secondary metabolites found in the oils possess healthy properties. The cholesterol levels of the oil samples showed that the oils contain an acceptable amount of cholesterol and the antibacterial activities of these oils showed that they have significant effects on the bacteria used in the study; hence, the results of these findings support the use of these oils as therapeutic agents